Report by the Comptroller and Auditor General. HC 764 aession 2001-2002, 25 April 2002: Government on the web II - Dunleavy, P; Margetts, H (National Audit Office, 2002)
A significant amount of taxpayers’ money is being spent in central and local government in introducing Internet-based services. I have found considerable progress since my previous report in 1999 but weaknesses in information across government on the usage of its web sites, performance indicators to measure progress and methodologies to assess the value added by e-government provision.